The increasing gap between words and deeds: teaching public affairs at the colleges of the army from academic year 1947 through academic year 1989 - Gardner, Paul Breen (Kansas State University, 2014)
After the Second World War, the leaders of the Department of the Army (DA) worked to inform those in the service that they had a duty to help the American people understand what the Army was doing to provide security for the nation. Their goal was for the public to have, at a minimum, the same amount of understanding of the Army as it had during World War II. To achieve this goal they believed that the officer corps had to be convinced that explaining to the public what the service was doing was in the best interest of the Army. The effort of the leaders to convince the officer corps was conducted by two primary means. First, the leaders made many public statements announcing that the Army would continue to inform the American people. Second, they added a requirement for those setting the curricula at the senior two schools of the service to provide instruction about the program that the Army had, which had three sub-programs, to update the American public. Between AY 1947 and 1989, the leaders continued to talk about the importance of informing the public. However, those approving the curricula at the two Colleges of the Army placed decreasing emphasis on educating students about what public affairs was and how to conduct it. This assertion is based on three primary findings. First, there is a clear decrease in the number of hours allocated to teaching about public affairs. Second, over the course of this period students were provided with fewer chances to apply what they were learning. Third, the coverage of the instruction went from covering at least two of the components of the Army’s program to at best only one. In the end a gap is clearly visible between what the leaders of the Army were saying regarding the importance of educating officers about public affairs and what was included in the curricula of these two schools: deeds did not match words.
Keywords: American history; Military history; Military studies; American History (0337); Military History (0722); Military Studies (0750)